Survei Motivasi Siswa dalam Pembelajaran Pjok Pada MAN 3 Seram Timur Kabupaten Seram Bagian Timur - Sadam Kelwarani; Idris Moh Latar; Jacob Anaktototy (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the level of learning motivation of PJOk in students of MAN 3 Seram Timur, East Seram Regency. Motivation is one of the important elements that is very influential in the PJOK learning process, this is in line with the understanding of motivation according to Rahmiyanti 2017, motivation is the urge to move someone to behave, this urge is found in someone who moves something in accordance with the impulse within him. Thus, when students have motivation to learn PJOK, it can be ascertained that the participation of these students in learning will look good, but on the other hand, when students do not have motivation to learn PJOK, automatically these students will always be indifferent to learning PJOK. This research design uses quantitative descriptive research. Quantitative descriptive research, aims to describe, record, and analyze quantitatively the conditions under study. This research was conducted at MAN 3 Seram Timur, Seram Timur Regency with a population of 170 students and a sample of 100 students. Sampling was carried out using the Random Sampling technique, the data analysis technique was using the Percentage Formula. The results of the research conducted showed that PJOK learning motivation in MAN 3 Seram Timur students, East Seram Regency, there were 6% (6 samples) had very high PJOK learning motivation, 10% (10 samples) had high PJOK learning motivation, 33% ( 33 samples) have moderate learning motivation of PJOK, 47% (47 samples) have low learning motivation of PJOK, and 4% (4 samples) have very very low motivation to learn PJOK.